1993
DOI: 10.1161/01.atv.13.8.1139
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid, lipoprotein cholesterol, and apoprotein distributions in selected US communities. The Atherosclerosis Risk in Communities (ARIC) Study.

Abstract: The distributions of plasma lipids, lipoproteins, and apoproteins of 14 524 female and male black and white participants 45 to 64 years old in the Atherosclerosis Risk in Communities (ARIC) Study are presented. All specimens were analyzed at a central laboratory. Mean total cholesterol levels increased with increasing age across all ages from 204 to 229 mg/dL (12%) in women and from 208 to 213 mg/dL (2%) in men. Triglyceride levels increased with age in women, remained stable in men, and were higher in whites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
79
5
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 53 publications
(20 reference statements)
17
79
5
4
Order By: Relevance
“…However, given the growing burden of obesity, metabolic disease, and insulin resistance in Canada, the increasing concentrations later in life may further reflect modifiable cardiovascular risk factors such as diet and sedentary lifestyle choices within the population. In contrast to the present study, previous studies have noted higher LDL concentrations in females, particularly postmenopause, when the protective effect of estrogens is lost (24,25 ). On the other hand, HDL declined with age in males but actually increased in females.…”
Section: Discussioncontrasting
confidence: 99%
“…However, given the growing burden of obesity, metabolic disease, and insulin resistance in Canada, the increasing concentrations later in life may further reflect modifiable cardiovascular risk factors such as diet and sedentary lifestyle choices within the population. In contrast to the present study, previous studies have noted higher LDL concentrations in females, particularly postmenopause, when the protective effect of estrogens is lost (24,25 ). On the other hand, HDL declined with age in males but actually increased in females.…”
Section: Discussioncontrasting
confidence: 99%
“…These results indicate a gender difference in responsiveness toward the risk factor that may be modulated by interactions with other genderspecific factors. In a similar manner, women have higher HDL concentrations than men, and changes in HDL may have a greater impact on the risk of cardiovascular disease in women than men (39 ). The National Cholesterol Education Program recognizes a possible differential impact of changes in HDL concentrations on men and women (40 ) and proposes more aggressive guidelines for women than men.…”
Section: Discussionmentioning
confidence: 99%
“…In the Atherosclerosis Risk in Communities (ARIC) study (36) carried out on men and women aged between 45-64 years of age, women, both black and white, had higher lipoprotein(a) levels than men. In addition, in postmenopausal women on hormone replacement therapy lipoprotein(a) as well as apolipoprotein B and low density lipoprotein cholesterol levels were lower than in non-replacement women.…”
Section: Resultsmentioning
confidence: 99%
“…In postmenopausal women several groups (34)(35)(36)(37) have reported changes in lipid and lipoprotein profiles, including an increase in lipoprotein(a), which can be reversed by sex-steroid therapy. The review of Radwanska (18) has shown that certain sex-steroids are capable of changing the lipid and lipoprotein levels, including the reduction of lipoprotein(a).…”
Section: Resultsmentioning
confidence: 99%